Analisis Faktor Risiko Kecelakaan Kerja dan Upaya Pencegahannya di Usaha Konveksi Sablon: Studi Kasus Inkside Sablon - Sinta Kurnia; Niken Widyastuti (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This research aims to analyze the risk factors of occupational accidents and identify effective prevention efforts within the context of Micro, Small, and Medium Enterprises (MSMEs), specifically at Inkside Sablon. This qualitative study, employing a case study approach, utilized in-depth interviews, participant observation, and documentary analysis for data collection. The findings indicate that occupational accident risk factors at Inkside Sablon are influenced by several aspects, including human factors such as lack of safety awareness and fatigue, environmental factors like inadequate ventilation and suboptimal lighting, and equipment factors such as non-ergonomic tools and insufficient maintenance. The prevention efforts implemented by Inkside Sablon are still partial and not well-structured, thus requiring the integration of more comprehensive safety programs, such as enhanced safety and health (OSH) training, provision of appropriate personal protective equipment (PPE), and improvements in management and supervision systems. It is expected that the implementation of these measures will increase worker awareness and reduce the number of occupational accidents, thereby creating a safer and more productive work environment